Pengaruh Penyuluhan terhadap Pengetahuan tentang Kehamilan Remaja di SMA Negeri 1 Banguntapan Bantul Yogyakarta - Sabrina Atsila Damayanti; Suyani Suyani (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2026)
Teenage pregnancy remains a reproductive health problem that increases the risk of complications during pregnancy, childbirth, and psychosocial problems. The low level of adolescent knowledge about teenage pregnancy is one of the factors contributing to the high incidence, so promotive and preventive efforts are needed through health education. This study aims to determine the effect of education on the knowledge of female adolescent about teenage pregnancy at SMAN (State Senior High School) 1 Banguntapan, Bantul, Yogyakarta. The study employed a pre-experimental design with a one-group pretest–posttest approach. The sample was 10th grade of female students selected using a proportionate stratified random sampling technique. The instruments used was a questionnaire on knowledge about teenage pregnancy and leaflets. Data analysis was performed using the Wilcoxon Signed Rank Test. The results showed a difference in average knowledge before and after education of 0.9841. The normality test obtained a p-value of 0.000, indicating that the data were not normally distributed, and was continued with the Wilcoxon test. The Wilcoxon test results showed a Z value of -5.522 with Asymp. Sig. (2-tailed) = 0.000, indicating a significant difference between the pretest and post- test scores. This indicates that health education has an impact on increasing female adolescent's knowledge about teenage pregnancy. Schools are expected to integrate reproductive health education on an ongoing basis with the support of health workers.